Pelayanan Holistik Rumah Cerdas Di Desa Tamanrejo, Kecamatan Limbangan, Kabupaten Kendal - Wahyudi Sri Wijayanto; Yoel Franpebri Panggabean (Journal Of Social Empowerment Publications, 2024)
Evangelism through holistic smart home services is very effective. Because in the process children are blessed and parents are also blessed. The Smart House in Tamanrejo Village in December 2023-February 2024 involves more than 10 members from STT Christ Alfa Omega Semarang. Coordinated by one person to organize the teaching planning. Before the implementation began, one of the representatives met with the head of the local RT to coordinate with the residents regarding the implementation of the smart home. Then after it is agreed. The coordinator divides tasks for the teaching team in teaching. In teaching in a smart home, the place used is one of the homes of residents who are willing to use it. It was agreed that the study house would be held once a week on Fridays at 16.00-17.00 WIB. In implementing the learning house, the teaching team provides teaching in accordance with the curriculum that has been created. Then after carrying out these activities, the teaching team also visited the children's parents. In this case, pre-evangelism can be carried out through curriculum studies in the home learning about character building. Apart from that, through visits to the families of the children being taught.